Faith and Reason: A Catholic Perspective on Epistemology - I Gede Januarsa; Setyaningrum susanti; Risa Musyayyada (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2024)
This paper explores the interplay between faith and reason within the Catholic intellectual tradition. It revisits foundational works of Thomas Aquinas and Augustine to provide a framework for understanding knowledge acquisition through divine revelation and rational inquiry. The article also addresses contemporary challenges in integrating faith with scientific advancements and secular ideologies.